Childhood-onset enthesitis-related arthritis leading to nephrotic syndrome due to secondary amyloidosis complicated by acute pulmonary embolism - The domino effect - Vishal Mangal; Bhaskar Datt; Arun Hegde; A W Kashif; Ankit Kumar; Jaspreet Kaur; Nidhi Goel; Anil Shankar Menon (Indian Journal of Rheumatology)
The prevalence of Juvenile idiopathic arthritis (JIA) in India is 0.001% among the population under 16 years old and 0.00029% among the total population. Of the total JIA population, enthesitis-related arthritis (ERA) constitutes 35% of the cases. In the past, chronic infections, mainly, tuberculosis were the most common cause of AA amyloidosis in India; however, chronic inflammatory arthropathies have become the most common cause of AA amyloidosis in India over the past three to four decades. In 95% of the patients with AA amyloidosis, the kidney is the most affected organ presenting as proteinuria of nephrotic syndrome. The prevalence of AA amyloidosis in JIA is estimated to be 7.7% and 3.1% among the ERA group, making it an infrequent association. This translates to one case of AA amyloidosis secondary to ERA per 1,00,000,00 population in India. Similarly, the incidence of pulmonary thromboembolism in patients with nephrotic syndrome is 7.8%. We present a case of a young male who was diagnosed with JIA-ERA at the age of 13 years with multiple flares in childhood had now developed nephrotic syndrome secondary to AA amyloidosis demonstrated on renal biopsy complicated by acute pulmonary embolism and occult hepatitis B infection. He was managed with anti-tumor necrosis factor inhibitor therapy with a favorable outcome. This is the first such case of multiple rare associations occurring together in a single patient to the best of our knowledge.